Boosting genome editing efficiency in human cells and plants with novel LbCas12a variants - Liyang Zhang; Gen Li; Yingxiao Zhang; Yanhao Cheng; Nathaniel Roberts; Steve E. Glenn; Diane DeZwaan-McCabe; H. Tomas Rube; Jeff Manthey; Gary Coleman; Christopher A. Vakulskas; Yiping Qi (Genome Biology, 2023)
Abstract Background Cas12a (formerly known as Cpf1), the class II type V CRISPR nuclease, has been widely used for genome editing in mammalian cells and plants due to its distinct characteristics from Cas9. Despite being one of the most robust Cas12a nucleases, LbCas12a in general is less efficient than SpCas9 for genome editing in human cells, animals, and plants. Results To improve the editing efficiency of LbCas12a, we conduct saturation mutagenesis in E. coli and identify 1977 positive point mutations of LbCas12a. We selectively assess the editing efficiency of 56 LbCas12a variants in human cells, identifying an optimal LbCas12a variant (RVQ: G146R/R182V/E795Q) with the most robust editing activity. We further test LbCas12a-RV, LbCas12a-RRV, and LbCas12a-RVQ in plants and find LbCas12a-RV has robust editing activity in rice and tomato protoplasts. Interestingly, LbCas12a-RRV, resulting from the stacking of RV and D156R, displays improved editing efficiency in stably transformed rice and poplar plants, leading to up to 100% editing efficiency in T 0 plants of both plant species. Moreover, this high-efficiency editing occurs even at the non-canonical TTV PAM sites. Conclusions Our results demonstrate that LbCas12a-RVQ is a powerful tool for genome editing in human cells while LbCas12a-RRV confers robust genome editing in plants. Our study reveals the tremendous potential of these LbCas12a variants for advancing precision genome editing applications across a wide range of organisms.